If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -25 = -13 Reorder the terms: -25 + 4x = -13 Solving -25 + 4x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 4x = -13 + 25 Combine like terms: -25 + 25 = 0 0 + 4x = -13 + 25 4x = -13 + 25 Combine like terms: -13 + 25 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 2(3y+6)4(3+2y)=350 | | 2r^2-13r-24=0 | | 3(8y-0.9)+3.6=25y | | 7z=28 | | 3(u+1)=-7u+33 | | -135-14x=-9x+35 | | 5r^2+19r-4=0 | | 49x^2=23 | | -3x+6(-x+6)=81 | | -8=-8w+6(w+2) | | 8r^2-14r+3=0 | | -6x+yb=c | | V=x(11-2x)(8.5-2x) | | 108/14 | | 0=12x^2+9x+1 | | 1/2(4q+12)=2+3(6-q) | | 4(p+8)-3p=32 | | -22+m=-71 | | 2(6y+3)=106 | | -6x-68=-x+67 | | -6x+by=c | | x+x+5265=14165 | | -3X^2+mx+n=0 | | (5x+6)(3x-1)= | | 8=n-12 | | 6x-5(-x+6)=25 | | (x)(x+8)=0 | | m-13=17 | | 9x=4(2x-5) | | a^2-a=4a+36 | | (2x+3)(3x-1)= | | 6x^3-48x^2=0 |